Cognitive screening assessment in Thai older adults: a prospective study of the reliability and validity of the Abbreviated Mental Test. Issue 1 (18th February 2021) - Tanglakmankhong, Kamonthip; Hampstead, Benjamin M; Ploutz-Snyder, Robert J; Potempa, Kathleen
Abstract : Purpose: The purpose of this paper is to examine the reliability and validity of the Abbreviated Mental Test (AMT) and the agreement with the Mini-Mental State Examination (MMSE). Design/methodology/approach: This cross-sectional study included 446 older adults who were recruited by cluster sampling from 200, 481 adults aged more than 60 years. For each participant, the AMT was administered by village health volunteers and, on a separate day, by a trained professional who also administered the MMSE. Descriptive statistics, Bland and Altman levels of agreement, and Receiver Operator Curves (ROCs) were used to analyze data. Findings: Administration of the AMT by village health volunteers during the annual health screening found cognitive impairment in only 1.12% of the sample. When the AMT was given to these same individuals by trained professionals, the rate of cognitive impairment was almost 24 times greater. Two items in the Thai AMT may require modification due to markedly elevated failure rates. At the cut score of 8, the sensitivity and specificity of the AMT relative to the MMSE were moderate (78.83 and 66.67%, respectively). The degree of agreement between AMT and MMSE was 0.49 ( p < 0.001) and the correlation between the difference scores and the mean is exceptionally low (0.048). Originality/value: Reliable and valid cognitive screening assessment requires the administrator to be well trained and the tools to be appropriate for the population. Although AMT is short and easy for a nonprofessional to administer, some items were not suitable due to construct validity and contextual issues.